A conceptual framework for the assessment of tropical secondary forest dynamics and sustainable development potential in Asia - Chokkalingam, U.; Smith, J.; Jong, W. de; Sabogal, C. (2001)
In this paper, we present an intensification model based on the intensity of exploitation and use of forests and forest lands as a relevant framework for analysing the appearance, dynamics, and evolution of different types of secondary forests. The systematic driving forces responsible for the disturbances and subsequent secondary forest re growth tend to change and evolve along this continuum. This dynamic, process oriented, long term framework draws on existing theories and models of the underlying factors of forest change relevant for tropical Asia, and emphasises factors related to secondary forests. We identify and characterise four general stages along this intensification continuum the extensive use stage, the intensive exploitation stage, the forest depleted stage, and the forest recovery stage. In the extensive use stage, secondary forests tend to be limited and largely arise from long rotation swidden agriculture. In the intensive exploitation stage, secondary forests tend to increase in absolute and proportional area, and arise mainly out of industrial and local logging activities and fires. In the forest depleted stage, natural forest cover is low and there is increasing interest in forest conservation, reforestation and sustainable management for timber, environmental and local needs. In the forest recovery stage, there is increased forest cover as a result of reforestation measures or regeneration with land use abandonment. This framework can help guide management and policy options for secondary forests based on threats and relative resource endowments, infrastructure, and the policy and institutional environment present in each stage. It could also be used to identify effective intervention points and to anticipate and prevent problem situations beforehand.